Prognostic value of plasma phenylalanine and gut microbiota-derived metabolite phenylacetylglutamine in coronary in-stent restenosis - Fu, Yuan; Yang, Yixing; Fang, Chen; Liu, Xinming; Dong, Ying; Xu, Li; Chen, Mulei; Zuo, Kun; Wang, Lefeng (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study was designed to explore the predictive value of plasma phenylalanine (Phe) and gut microbiota-derived metabolite phenylacetylglutamine (PAGln) in coronary in-stent restenosis (ISR). Methods: Patients with coronary ISR, in-stent hyperplasia (ISH), and in-stent patency (ISP) were retrospectively enrolled in this study. Multivariable logistic regression analyses were used to identify independent risk factors of ISR. The predictive value of plasma Phe and PAGln levels was evaluated by receiver operating characteristic (ROC) curve analysis. The areas under the ROC curve (AUCs) were compared using the Z-test. The correlation between PAGln and clinical characteristics were examined using Spearman’s correlation analysis. Results: Seventy-two patients (mean age, 64.74 ± 9.47 years) were divided into three groups according to coronary stent patency: ISR (n = 28), ISH (n = 11), and ISP (n = 33) groups. The plasma levels of Phe and PAGln were significantly higher in the ISR group than in the ISP group. PAGln was positively associated with the erythrocyte sedimentation rate, homocysteine, SYNTAX score, triglyceride to high-density lipoprotein ratio, Phe, and microbiota-related intermediate metabolite phenylacetic acid (PA). In the ISR group, with the aggravation of restenosis, PAGln levels were also elevated. In multivariate regression analyses, Phe, PAGln and SYNTAX score were independent predictors of coronary ISR (all P <0.05). In the ROC curve analyses, both Phe (AUC = 0.732; 95% confidence interval [CI], 0.606–0.858; P = 0.002) and PAGln (AUC = 0.861; 95% CI, 0.766–0.957; P < 0.001) had good discrimination performance in predicting coronary ISR, and the predictive power of PAGln was significantly better (P = 0.031). Conclusions: Plasma Phe and PAGln are valuable indices for predicting coronary ISR, and gut microbes may be a promising intervention target to prevent ISR progression.